Effect of Land Use and Land Cover Change on Inundation and Flood Loss Value in Lumajang District - Regina Salsabila Athallah; Agus Suharyanto; Indradi Wijatmiko (The Indonesian Institute of Science and Technology Research, 2026)
This study examines the relationship between land cover change and the extent of inundation and the value of economic losses due to flooding in Lumajang district in 1995, 2014, and 2023. Using a spatial approach based on satellite imagery and hydraulic simulation, as well as the ECLAC method in calculating losses, this study shows that the loss of natural land cover, such as forests and wetlands, as well as the expansion of residential areas, contributed significantly to the increase in inundation intensity and economic losses. These findings are important for spatial planning that is adaptive to hydrometeorological disaster risks. In addition, this research also supports the implementation of mitigation policies based on spatial and hydrological data that are appropriate to the conditions of the Jatiroto watershed.